Preparation system of scratch-resistant coating for solar cell front panel

By using scratch-resistant coating preparation system on the front panel of the solar cell, nanoparticles with core-shell structures are formed and produced by mixing components such as ethylene-vinyl acetate copolymer resin, acrylate resin and modified nano-silicon nitride. The bubble treatment solves the problem that the coating is prone to scratch and fall off in the prior art, achieves good adhesion and wear resistance, and maintains high light transmittance.

CN222510936UActive Publication Date: 2025-02-21JIANGSU SHUANGXING COLOR PLASTIC NEW MATERIALS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202323512873.4
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2025-02-21
Estimated Expiration
2033-12-21

AI Technical Summary

Technical Problem

Prior Art When applying hardened coating to solar cell front panels, it is necessary to perform corona treatment on PVDF films to improve binding force, but this will reduce the light transmittance and cannot meet the light transmittance requirements of the front panel, resulting in the coating being easily The problem of scratches and falls off.

Method used

Using a scratch-resistant coating preparation system, nanoparticles with core-shell structure are formed by mixing and reacting components such as ethylene-vinyl acetate copolymer resin, acrylate resin, modified nano-silicon nitride, etc., and combined with foaming treatment, to ensure that The coating has good adhesion and wear resistance under high temperature environments.

Benefits of technology

It achieves good adhesion and excellent scratch and wear resistance of the front panel coating of the solar cell without reducing the light transmittance, avoiding the problem of easy scratching and falling off in actual use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222510936U_ABST
    Figure CN222510936U_ABST
Patent Text Reader

Abstract

The utility model discloses a preparation system of a scratch-resistant coating for a front panel of a solar cell. The preparation system at least comprises a first mixing tank, a second mixing tank and a third mixing tank, wherein the first mixing tank is used for mixing ethylene-vinyl acetate copolymer resin and dimethyl sulfoxide to obtain a first mixed solution; the second mixing tank is used for mixing acrylate resin and tetraisopropyl titanate to obtain a second mixed solution; the third mixing tank is used for mixing hexadecyl trimethyl ammonium bromide, dodecyl bis (hydroxyethyl) methyl ammonium chloride and modified nano silicon nitride to obtain a third mixed solution; the reaction kettle is used for mixing and reacting the first mixed solution, the second mixed solution and the third mixed solution; outlets of the first mixing tank, the second mixing tank and the third mixing tank are connected with an inlet of the reaction kettle. The scratch-resistant coating prepared by the preparation system disclosed by the utility model can ensure that the scratch-resistant coating of the front panel of the solar cell has good adhesive force and excellent scratch resistance and wear resistance in a high-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to an anti-scratch coating of a solar cell front plate composited with a polymer material, in particular to a preparation system of the anti-scratch coating for the solar cell front plate. Background Art

[0002] Solar cell modules are usually composed of front panels, packaging materials, solar cells, back panels and other structures. Most solar cell front panels are made of glass, which has high strength and good light transmittance, but is heavy, cannot bend greatly, and is prone to cracking. Polymer materials are increasingly attracting attention as front panel materials to replace glass. Existing polymer composite front panels generally use fluorocarbon resin and PET base film to form a transparent front panel. The difference between the front panel and the back panel is that discoloration and delamination will reduce the light transmittance of the front panel, which will directly lead to optical loss.

[0003] CN 112852194 B discloses a hardening coating, which is used to solve the problems of low surface hardness and poor wear resistance of the existing solar cell back panel. The hardening coating of the prior art includes the following raw material components by mass percentage: 70% to 90% gel, 5% to 25% multifunctional acrylic monomer and / or prepolymer, and 0.1% to 5% curing agent; wherein the gel contains a titanium-containing compound, and the multifunctional acrylic monomer and / or prepolymer is a monomer and / or prepolymer containing at least 3 acrylate groups. The embodiment of the prior art records that the hardening coating containing the gel is coated on the surface of the PVDF film after corona treatment, and is baked at 120-150°C for 10 minutes to complete curing to form a hardened coating. The hardening coating of the prior art is suitable for improving the wear resistance of the solar cell back panel.

[0004] However, it is known that the surface energy of PVDF film is extremely low and it is not easy to firmly bond with most materials. The above-mentioned prior art performs corona treatment on PVDF film before applying hardening coating in order to increase the surface roughness of PVDF film and improve the bonding force with hardening coating. Performing corona treatment on PVDF film will reduce the light transmittance of back sheet, which is no problem for solar cell back sheet, but it is unacceptable for solar cell front sheet, because the main function of front sheet is to increase sufficient light transmittance to improve photoelectric conversion efficiency.

[0005] Therefore, if the PVDF film is not subjected to corona treatment, the bonding strength between the hardened coating and the PVDF film is difficult to reach the adhesion level recorded in the prior art, and the hardened coating is easily scratched and falls off. For example, ordinary solar cells are usually installed in the open air with plenty of sunshine, and there is usually a lack of water sources around. It is very difficult to wash the surface of the solar cell with water. In many cases, the only way is to use tools to dry wipe the front panel of the solar cell. If the bonding strength between the hardened coating and the front panel surface is not enough, it is easy to be scratched, scraped off, or partially fall off. Summary of the invention

[0006] The technical problem to be solved by the present application is to provide a system for preparing a scratch-resistant coating for a solar cell front panel, so as to reduce or avoid the above-mentioned problems.

[0007] To solve the above technical problems, the present application proposes a system for preparing a scratch-resistant coating for a solar cell front panel, wherein the preparation system at least includes: a first mixing tank for mixing ethylene-vinyl acetate copolymer resin and dimethyl sulfoxide to obtain a first mixed liquid; a second mixing tank for mixing acrylate resin and tetraisopropyl titanate to obtain a second mixed liquid; a third mixing tank for mixing hexadecyltrimethylammonium bromide, dodecylbis(hydroxyethyl)methylammonium chloride and modified nano-silicon nitride to obtain a third mixed liquid; and a reactor for mixing the first mixed liquid, the second mixed liquid and the third mixed liquid; wherein the outlets of the first mixing tank, the second mixing tank and the third mixing tank are connected to the inlet of the reactor.

[0008] Preferably, the inlet of the third mixing tank is connected to a modification device for performing surface modification treatment on nano-silicon nitride.

[0009] Preferably, the modification treatment equipment comprises: a dispersion tank for dispersing nano silicon nitride into a mixed solution of tetraethyl silicate, ethanol and hydrochloric acid, the outlet of the dispersion tank is connected to a freeze-drying spray device, and the outlet of the freeze-drying spray device is connected to the third mixing tank.

[0010] The scratch-resistant coating prepared by the preparation system of the present application reduces the surface performance of high-hardness materials through core-shell structured nanoparticles, and at the same time highlights the high-hardness particles through foaming treatment, which can ensure that the scratch-resistant coating of the front panel of the solar cell has good adhesion, excellent scratch resistance and wear resistance in a high-temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] The following drawings are only intended to illustrate and explain the present application, and do not limit the scope of the present application.

[0012] Figure 1 Shown is a schematic structural diagram of a solar cell front panel according to a specific embodiment of the present application.

[0013] Figure 2 Shown is a schematic structural diagram of a system for preparing a scratch-resistant coating for a solar cell front panel according to a specific embodiment of the present application. DETAILED DESCRIPTION

[0014] In order to have a clearer understanding of the technical features, purposes and effects of the present application, the specific implementation of the present application is now described with reference to the accompanying drawings, wherein the same components are numbered the same.

[0015] Figure 1 A schematic diagram of the structure of a solar cell front panel is shown, which at least includes a PET film 10, and the PET film 10 is bonded to a fluorocarbon resin protective film 30 through an adhesive layer 20. The fluorocarbon resin protective film 30 faces the sun and can provide excellent barrier properties and weather resistance. The PET film 10 provides a supporting skeleton for the entire front panel, and a weather-resistant coating or a protective layer can be further provided on the inner side of the PET film 10. The fluorocarbon resin includes but is not limited to polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polytrifluorochloroethylene (FEVE) and / or polyvinyl fluoride (PVF). In a specific embodiment, the thickness of the PET film 10 is 100-200μm, the thickness of the adhesive layer 20 is 3-5μm, and the thickness of the fluorocarbon resin protective film 30 is 10-20μm.

[0016] Furthermore, in order to improve the scratch resistance of the fluorocarbon resin protective film 30 located on the surface, the present application applies a scratch-resistant coating 40 formed by curing the scratch-resistant coating of the present application on the outside of the fluorocarbon resin protective film 30. As described in the background art, in order to ensure the light transmittance of the front plate, the outer surface of the fluorocarbon resin protective film 30 cannot be roughened, so the scratch-resistant coating 40 needs to have a strong bonding ability with the fluorocarbon resin protective film 30 and also have good light transmittance.

[0017] In a specific embodiment of the present application, the anti-scratch coating for solar cell front plate of the present application is preferably composed of the following components in parts by weight: 20-60 parts by weight of ethylene-vinyl acetate copolymer resin, 10-50 parts by weight of dimethyl sulfoxide, 120-160 parts by weight of acrylic resin, 12-16 parts by weight of hexadecyl trimethyl ammonium bromide, 12-16 parts by weight of dodecyl bis-hydroxyethyl methyl ammonium chloride, 22-26 parts by weight of tetraisopropyl titanate and 4-12 parts by weight of modified nano silicon nitride, and 0.2-0.6 parts by weight of initiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide. Among them, ethylene-vinyl acetate copolymer adopts EVA 210 of Mitsui of Japan, and the mass percentage of vinyl acetate polymer contained therein is 28%. The coating of the present application performs foaming treatment on the nano-particle material to form a surface structure with protruding nano-particles, and uses the high hardness of the nano-particles protruding from the surface layer to provide anti-scratch performance.

[0018] The preparation method of the anti-scratch coating of the present application is as follows: 20-60 parts by weight of ethylene-vinyl acetate copolymer resin and 10-50 parts by weight of dimethyl sulfoxide are stirred at a speed of 200-300 rpm for 30-60 minutes to obtain a first mixed solution. 120-160 parts by weight of acrylic resin and 22-26 parts by weight of tetraisopropyl titanate are mixed and stirred at a speed of 200-300 rpm for 30-60 minutes to obtain a second mixed solution. 12-16 parts by weight of hexadecyltrimethylammonium bromide, 12-16 parts by weight of dodecylbis(hydroxyethyl)methylammonium chloride and 4-12 parts by weight of modified nano silicon nitride are mixed and stirred at a speed of 200-300 rpm for 30-60 minutes to obtain a third mixed solution. The first mixed liquid, the second mixed liquid and the third mixed liquid are added to a reaction kettle, and then 0.2-0.6 parts by weight of an initiator are added, and the mixture is mixed at a rotation speed of 1500-2000 rpm for 30-60 minutes to prepare the anti-scratch coating of the present application.

[0019] The prepared anti-scratch coating is coated on the outer surface of the fluorocarbon resin protective film 30 of the front plate, irradiated with ultraviolet light for 60-180 seconds, and then baked at 80° C.-100° C. for 60-120 seconds, and cured to obtain the anti-scratch coating 40 .

[0020] Among them, the preparation steps of the nano-modified silicon nitride are: tetraethyl silicate and ethanol are mixed and stirred in a mass ratio of 1:1.2, 20% hydrochloric acid is added dropwise, the pH value is adjusted to 2, and the temperature is stirred at 60°C for 1-1.5 hours to obtain a liquid mixture, 1000 parts by weight of the liquid mixture is taken, 10-100 parts by weight of nano-silicon nitride is added, and the mixture is stirred for 60-120 minutes to fully mix to obtain a dispersed mixture; the dispersed mixture is subjected to freeze-drying spray, and particles with a particle size of 10-20nm are screened to obtain nano-modified silicon nitride. The nano-modified particles are silicon nitride coated with silicon dioxide, which reduces the surface performance of silicon nitride, and the solvent is fully removed by freeze-drying spray to improve the weather resistance of the subsequent coating. Relatively speaking, the gel coating treatment scheme of the prior art is removed by evaporation, and solvent residues are prone to occur, which has a great impact on performance.

[0021] Correspondingly, such as Figure 2 As shown, the present application also proposes a system for preparing a scratch-resistant coating for a solar cell front panel. Figure 2 In the specific embodiment shown, the preparation system of the present application at least includes: a first mixing tank 100 for mixing ethylene-vinyl acetate copolymer resin and dimethyl sulfoxide to obtain a first mixed solution; a second mixing tank 200 for mixing acrylate resin and tetraisopropyl titanate to obtain a second mixed solution; a third mixing tank 300 for mixing hexadecyltrimethylammonium bromide, dodecylbis(hydroxyethyl)methylammonium chloride and modified nano silicon nitride to obtain a third mixed solution; and a reactor 400 for mixing the first mixed solution, the second mixed solution and the third mixed solution; wherein the outlets of the first mixing tank 100, the second mixing tank 200 and the third mixing tank 300 are connected to the inlet of the reactor 400. The inlet of the third mixing tank 300 is connected to a modification treatment device 500 for surface modification of nano silicon nitride.

[0022] Further, in another specific embodiment of the present application, Figure 2 As shown, the modification treatment equipment 500 includes: a dispersion tank 501 for dispersing nano silicon nitride into a mixed solution of tetraethyl silicate, ethanol and hydrochloric acid, the outlet of the dispersion tank 501 is connected to a freeze-drying spray device 502, and the outlet of the freeze-drying spray device 502 is connected to the third mixing tank 300.

[0023] Example

[0024] The components in the following examples are replaced by the following letters to simplify the table content.

[0025] Ethylene-vinyl acetate copolymer resin: A

[0026] Dimethyl sulfoxide: B

[0027] Acrylic resin: C

[0028] Hexadecyltrimethylammonium bromide: D

[0029] Dodecyl bis(hydroxyethyl)methyl ammonium chloride: E

[0030] Tetraisopropyl titanate: F

[0031] Nano-modified silicon nitride: G

[0032] 2,4,6-Trimethylbenzoyl-diphenylphosphine oxide: H

[0033] According to the raw material weight parts and parameters in the following table, anti-scratch coatings for solar cell front sheets were prepared according to the above methods.

[0034]

[0035]

[0036] The anti-scratch coating prepared above is applied on Figure 1 The outermost side of the multi-layered solar cell front sheet is irradiated with ultraviolet light for 60-180 seconds, and then baked at 80°C-100°C for 60-120 seconds to form a scratch-resistant coating 40. A biaxially oriented polyester film with a thickness of 100-200 μm is used as the PET film 10, and a 10-20 μm PVDF protective film is bonded to the surface of the PET film 10 through a 3-5 μm adhesive layer 20 as a fluorocarbon resin protective film 30, and the thickness of the anti-scratch coating layer after curing is 2-5 μm.

[0037] The front plate prepared above was subjected to an accelerated aging test at 120° C. for 48 hours with a test humidity of 100%.

[0038] Among the test items, the transmittance test is the visible light transmittance. The adhesion test adopts the hundred-grid test. After the coating surface is gridded according to ASTMD3359, 3M tape is used to tear off the coating surface 180°, and the integrity of the surface paint film is observed. Repeat 3 times. The surface hardness test (scratch hardness) is carried out according to ASTM D3363 at a 45° inclination angle and a load of 1kg. A 6H to 6B pencil is used to draw a 1 / 4 inch note on the coating surface. Observe whether there are scratches on the coating surface. Repeat 3 times. Surface wear resistance test (steel wool method): refer to ASTM F2496, steel wool is #0000, pressure is 500g / cm2, stroke is 3.3cm, speed is 80 times / min, and a magnifying glass is used to observe whether there are scratches on the surface appearance every 200 times. When scratches appear, stop and record the number of frictions.

[0039] The test results are shown in the following table.

[0040]

[0041]

[0042] The results show that the anti-scratch coating of the present application can ensure that the anti-scratch coating of the solar cell front panel has good adhesion, excellent anti-scratch and wear resistance, and excellent light transmittance and low haze under high temperature environment.

[0043] Those skilled in the art should understand that although the present application is described in the form of multiple embodiments, not every embodiment contains only one independent technical solution. Such description in the specification is only for the sake of clarity, and those skilled in the art should understand the specification as a whole and regard the technical solutions involved in each embodiment as being able to be combined into different embodiments to understand the scope of protection of the present application.

[0044] The above description is only an illustrative embodiment of the present application and is not intended to limit the scope of the present application. Any equivalent changes, modifications and combinations made by any technician in the field without departing from the concept and principle of the present application shall fall within the scope of protection of the present application.

Claims

1. A system for preparing a scratch-resistant coating for a solar cell front plate, characterized in that: The preparation system at least includes: a first mixing tank for mixing ethylene-vinyl acetate copolymer resin and dimethyl sulfoxide to obtain a first mixed liquid; a second mixing tank for mixing acrylate resin and tetraisopropyl titanate to obtain a second mixed liquid; a third mixing tank for mixing hexadecyltrimethylammonium bromide, dodecylbis(hydroxyethyl)methylammonium chloride and modified nano-silicon nitride to obtain a third mixed liquid; and a reactor for mixing the first mixed liquid, the second mixed liquid and the third mixed liquid; wherein the outlets of the first mixing tank, the second mixing tank and the third mixing tank are connected to the inlet of the reactor; the inlet of the third mixing tank is connected to a modification treatment device for surface modification of nano-silicon nitride; the modification treatment device includes: a dispersion tank for dispersing nano-silicon nitride in a mixed solution of tetraethyl silicate, ethanol and hydrochloric acid, the outlet of the dispersion tank is connected to a freeze-drying spray device, and the outlet of the freeze-drying spray device is connected to the third mixing tank.

Citation Information

Patent Citations

  • A hardening coating, its preparation method and application, and a solar cell backsheet.

    CN112852194B